The politics of IWRM in southern Africa - Mehta, L.; Alba, R.; Bolding, A.; Denby, K.; Derman, A.; Hove, T.; Manzungu, Emmanuel; Movik, S.; Prabhakaran, P.; van Koppen, Barbara (Informa UK Limited, 2014)
This article offers an approach to the study of the evolution, spread and uptake of integrated water resources management (IWRM). Specifically, it looks at the flow of IWRM as an idea in international and national fora, its translation and adoption into national contexts, and the on-the-ground practices of IWRM. Research carried out in South Africa, Zimbabwe and Mozambique provides empirical insights into the politics of IWRM implementation in southern Africa, the interface between international and national interests in shaping water policies in specific country contexts, and the on-theground challenges of addressing equity, redress and the reallocation of water.